Emerging therapy options for IgG4-related disease. (4th May 2021) - Lanzillotta, Marco; Fernàndez-Codina, Andreu; Culver, Emma; Ebbo, Mikael; Martinez-Valle, Fernando; Schleinitz, Nicolas; Della-Torre, Emanuel
ABSTRACT: Introduction: Awareness of IgG4-related disease (IgG4-RD) is increasing worldwide and specialists are now familiar with most of its clinical manifestations and mimickers. IgG4-RD promptly responds to glucocorticoids and repeated courses are typically used to induce and maintain remission because the disease relapses in most patients. If left untreated, it can lead to organ dysfunction, organ failure and death. Advancement in our understanding of IgG4-RD pathogenesis is leading to the identification of novel therapeutic targets and emerging treatments are now setting the stage for personalized therapies for the future. Areas covered: This review focuses on emerging treatment options for IgG4-RD based on our advancing understanding of disease pathophysiology. Research was performed in the English literature on Pubmed and clinicaltrials.gov databases. Expert opinion: Glucocorticoids remain the first-line induction treatment for the multi-organ manifestations of IgG4-RD. Alternative immunosuppressive agents for maintaining remission are warranted in order to avoid long-term steroid toxicity, and to offer a more mechanistic and personalized therapeutic strategy. Targeting B and T-lymphocyte activation represents the most promising approach, but randomized controlled trials are eagerly awaited to confirm positive preliminary experiences reported in case series and small cohort studies.